Units of selection - Suárez, Javier; Lloyd, Elisabeth Anne 1956- (Cambridge elements, 2023)
'Unit of selection' is a polysemic expression, meaning interactor, replicator/reproducer or manifestor of adaptation/type-1 agent in today's biological research. This Element presents each of these concepts and demonstrates the necessity of their isolation